Between Scylla and Charybdis: Brexit as fate and trap. Issue 2 (September 2016) - Thompson, Helen
Abstract : From the Wilson and Heath governments' early, uneasy embrace of Brussels onwards, the contradictions in the UK's insistence on monetary sovereignty within the single market put it on an outward trajectory from Europe, arguesHelen Thompson . However, Brexit may intensify more conflicts of interest than it resolves.